STUDENTS’ CAPABILITY IN UNDERSTANDING WRITTEN TEXTS OF THE SECOND YEAR STUDENTS OF RSBI CLASS AT SMP N I WONOGIRI - SUSANTO, DANANG (2011)
The objectives of this study are (1) to describe the students’ capability in understanding written texts of the second year students of RSBI class at SMP N I Wonogiri, (2) to describe the problems faced by the second year students in understanding written texts, and (3) to describe the causes of problems faced by the second year students in understanding written texts. The study was done in SMP N I Wonogiri. As the sample , the writer took 23 students at VIIIc of RSBI class. The writer conducted treatment to the students in the form of the test. The type of test is multiple choice with four option and consists of 50 items. After collecting the data and analyzing them by using the formula, the writer described the result of the study. The writer found that the capability of the students in understanding the written texts can be divided into three level mastery, they are (1) fair level is 4. 35 % (1 student), (2) good level is 60. 87 % (14 students), and (3) the students who belong to excellent level is 34. 78 % (8 students). The problems faced by the students in understanding written texts are (1) understanding reference in the reading texts, (2) understanding vocabulary, and (3) understanding the paragraph development. The causes of the problems faced by the students are (1) the teacher did not motivate the students to improve their reading skill because in teaching process the teacher does not equip reading strategy to motivate the students in improving their reading skill such as giving reading journal, predicting unfamilar words in the context of the complex sentences, etc. (2) the students’ vocabulary and grammar are still limited because in teaching process the teacher usually focuses on the definition, parts, and questions of the written texts itself so when the students find complex sentences in the written texts they cannot comprehend it well. In conclusion, the students’ capability in understanding written texts at SMP N I Wonogiri is go